1994
DOI: 10.1161/01.cir.89.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome after valve replacement for rheumatic mitral regurgitation in the era of chordal preservation.

Abstract: When preoperative end-systolic diameter is more than 50 mm, a poor postoperative outcome is predicted despite chordal preservation in relatively young patients with rheumatic mitral regurgitation, and alternative strategies should therefore be considered. When preoperative end-systolic diameter is 40 mm or less, an excellent outcome is predicted, and close observation without surgery would appear to be reasonable in the absence of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(69 citation statements)
references
References 24 publications
5
63
1
Order By: Relevance
“…Therefore, the rate of survivors free from important symptoms, in 5 years, was 67.5%. In contrast with the South African study 4 , rheumatic disease was not the only cause found in our patients that could explain the difference in our results. However, our patients with mitral regurgitation had a decrease in systolic diameter and improvement in Functional Class.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, the rate of survivors free from important symptoms, in 5 years, was 67.5%. In contrast with the South African study 4 , rheumatic disease was not the only cause found in our patients that could explain the difference in our results. However, our patients with mitral regurgitation had a decrease in systolic diameter and improvement in Functional Class.…”
Section: Discussioncontrasting
confidence: 99%
“…Several indexes of left ventricular function assessment have been studied to help the prognosis of this disease after mitral valve replacement [1][2][3][4][5][6][7] . Even small enhancements in end-systolic left ventricular diameter in the preoperative period imply an increased risk of left ventricular dysfunction in the postoperative period 1,4 . Because of the poor surgical results found in patients with mitral regurgitation and end-systolic diameter ≥ 51mm, an alternative treatment has been proposed for these patients 4 .…”
mentioning
confidence: 99%
“…Despite this drawback,Fuster and his colleague have shown success in complete chordal preservation and better results in patients with rheumatic heart disease 13 . Similar results of improved survival and left ventricular function in rheumatic heart disease were reported by others [15][16][17] .…”
supporting
confidence: 89%
“…13,25 MR causes volume overload with LA enlargement 26,27 and LV remodeling 8,28,29 and induces BNP activation. 9,10 The present study confirms BNP activation in chronic organic MR and shows that it is biologically active, with parallel cGMP elevation.…”
Section: Rationale Of the Studymentioning
confidence: 99%